Formal [4+1] Cyclization of ortho‐ or para‐Quinone Methides with 3‐Chlorooxindoles: Synthesis of 3, 2′‐Tetrahydrofuryl Spirooxindoles. Issue 9 (10th August 2021) - Tian, Xiaochen; Zhang, Xiaoli; Hou, Xiaohan; Ren, Weiwu; Li, Xiaoyang; Zhao, Fei; Tao, Houchao; Wang, Yang
Abstract: A base promoted formal [4+1] cycloaddition of ortho ‐ and para ‐quinone methides with 3‐chlorooxindoles is reported to afford various functionalized 3, 2′‐tetrahydrofuryl spirooxindoles in high yields under mild conditions. An unexpected reversal in diastereoselectivity was observed from these two types of reactions. Computational studies have provided insight into the origin of diastereoselection, and different configurations of 1, 4‐addition and 1, 6‐addition at the oxindole carbanionic center are found to give rise to different diastereomers. The anti‐tumor activity of these structurally unique spirooxindole derivatives is reported. Abstract : A base promoted formal [4+1] cycloaddition of ortho ‐ and para ‐quinone methides with 3‐chlorooxindoles is reported to afford various functionalized 3, 2'‐tetrahydrofuryl spirooxindoles with an unexpected reversal diastereoselectivity. Different configurations of 1, 4‐addition and 1, 6‐addition at the oxindole carbanionic center are found to the origin of diastereoselection through DFT calculations. These structurally unique spirooxindole derivatives show promising anti‐tumor activity.